Diagnostic potential of urinary monocyte chemoattractant protein‐1 for Alzheimer's disease and amnestic mild cognitive impairment. (22nd May 2020) - Xu, Y.; Shen, Y.‐Y.; Zhang, X.‐P.; Gui, L.; Cai, M.; Peng, G.‐P.; Pan, X.‐D.; Zhang, J.; Gan, D.; Li, B.; Cheng, H.‐P.; Deng, J.; et al.
Abstract : Background and purpose: The chemokine monocyte chemoattractant protein‐1 (MCP‐1) is involved in the pathogenesis of Alzheimer's disease (AD). This study aimed to investigate whether urinary MCP‐1 can distinguish patients with AD, patients with amnestic mild cognitive impairment (aMCI) and cognitively normal (CN) subjects. Methods: A total of 754 participants, including 97 patients with AD, 50 patients with aMCI and 84 age‐ and sex‐matched CN controls as well as a cohort of 523 CN subjects of different ages, were enrolled from five hospitals located in different areas of China. Urinary MCP‐1 levels were determined using enzyme‐linked immunosorbent assays. The correlations between urinary MCP‐1 levels and cognition test scores or age were analysed. The optimal diagnostic sensitivity and specificity were determined using receiver operating characteristic curve analysis. Results: In the cohort of CN subjects of different ages, urinary MCP‐1 levels increased with ageing and were correlated with age. The urinary MCP‐1 levels were higher in females than in males. In the cohort composed of patients with AD, aMCI and age‐ and sex‐matched CN controls, urinary MCP‐1 levels were significantly higher in patients with AD and aMCI than in CN controls. There were no differences in urine MCP‐1 levels between the AD group and the aMCI group. The urinary MCP‐1 levels were correlated with the Mini‐Mental State Examination scores and age, and were able to differentiate patients with AD and aMCI from CN subjects. Conclusions: Urinary MCP‐1 is a potential biomarker for the diagnosis of AD and aMCI.